Handbook of pharmaceutical analysis by HPLC - Ahuja, Satinder, 1933-; Dong, M. W. (Elsevier Academic Press, 2005)
High pressure liquid chromatography & ndash;frequently called high performance liquid chromatography (HPLC or, LC) is the premier analytical technique in pharmaceutical analysis and is predominantly used in the pharmaceutical industry. Written by selected experts in their respective fields, the Handbook of Pharmaceutical Analysis by HPLC Volume 6, provides a complete yet concise reference guide for utilizing the versatility of HPLC in drug development and quality control. Highlighting novel approaches in HPLC and the latest developments in hyphenated techniques, the book captures the essence of major pharmaceutical applications (assays, stability testing, impurity testing, dissolution testing, cleaning validation, high-throughput screening, * A complete reference guide to HPLC * Describes best practices in HPLC and offers 'tricks of the trade' in HPLC operation and method development * Reviews key HPLC pharmaceutical applications and highlights currents trends in HPLC ancillary techniques, sample preparations, and data handling.
Keywords: High performance liquid chromatography -- Methodology.; Drugs -- Analysis.; elektronické knihy; electronic books